Clinical and Oncological Outcome of Chondroblastic Osteosarcoma: A Single Institutional Experience - Vyas, Ronak (Indian J Orthop, 2020)
INTRODUCTION: Chondroblastic osteosarcoma is an aggressive bone tumor characterized by chondroid matrix production with variable cellularity. This retrospective study is aimed to assess the demographic distribution, clinical behavior and oncological outcome of chondroblastic osteosarcoma. METHODS: 27 patients (14 males, 13 females) with chondroblastic osteosarcoma were included. The site of involvement included: proximal tibia (41%), distal femur (26%) and distal tibia (15%).The mean age of patients was 17 years (S.D: 6.9 years) (range 6–45 years). RESULTS: Painful swelling was the main complaint in all cases. Two patients were classified as Enneking III (lung) stage and the remaining patients had Enneking IIB stage. Post-neoadjuvant chemotherapy limb sparing surgery was performed in 70% of cases while in 30% of cases limb amputation was done. On histopathological examination of specimens mean necrosis was 64% (20–95%). Disease free survival (DFS) at 2 years was 46.4% and at 4 years was 27.9%. Median disease free survival was 24 ± 10.30 months. Overall survival (OS) at 2 years was 53.3% and at 4 years was 16.6%. Median overall survival is 28 ± 5.93 months. CONCLUSIONS: Chondroblastic osteosarcoma is associated with poor prognosis, high recurrence rate and metastatic potential with dismal long-term survival. Chondroblastic osteosarcoma is an aggressive histological variant of conventional osteosarcoma with frequent location around the knee joint, affecting young population. Chemotherapy with Methotrexate, Adriamycin, Cisplatin (MAP) regimen is a well-tolerated regimen, resulting in limb salvage surgery in majority of the cases.